COMFORT TEMPERATURE AND LIGHTING INTENSITY: ERGONOMICS OF LABORATORY ROOM MACHINE TOOLS - Idkhan, A. Muhammad; Baharuddin, Fiskia Rera (Three E Science Institute, 2019)
Laboratories that meet ergonomic standards will support the learning process, both academically and technically, to facilitate the growth and development of skills. This study aims to uncover and provide an overview and information about laboratory ergonomics standards which include thermal comfort (temperature), workspace laboratory lighting. This study uses a quantitative approach with a survey method carried out in the Machine Tool Unit Laboratory of the Department of Mechanical Engineering Education with a population of 60 students who are carrying out practicum. Techniques using direct observation and measurement. Lux Meter to measure lighting and then Digital Thermometer which functions to measure temperature at the observation point in the laboratory. Data collection starting at 07.00 until 12.00 and in the afternoon starting from 13.00 to 16.00, which is the time to do work activities. Measurements made at ten observation points the results showed that; (1) thermal comfort (temperature) with a value of 30.44 degrees Celsius, while the ideal practical standard ranges from 24 ? 27 degrees Celsius; (2) Lighting with a value of 422.14 Lux while the ideal practice standard ranges from 500 ? 1000 Lux. These results indicate that there is a tendency for temperature and lighting in laboratory rooms under conditions that are less than the standard set. To increase work productivity, these factors can cause less concentration and stress at work.